Lymphangioma of the buccal mucosa: A case report with a literature review - Chandrashekhar Pammar; Vijayalakshmi S Kotrashetti; Ramakant Nayak; Jagadish Hosmani (Wolters Kluwer Medknow Publications, 2015)
Lymphangioma is a benign, hamartomatous tumor of the lymphatic system. It is usually found in the head and neck region and is widely regarded as a developmental lesion rather than a true neoplasia. Most lymphangiomas are present at birth. In head and neck area, the most common location is the submandibular region, followed by the parotid gland. When lymphangioma occurs in the oral cavity, the anterior two third of the tongue is most commonly affected. The occurrence of lymphangioma in other parts of the oral cavity is very uncommon. Here, we report an unusual case of lymphangioma of buccal mucosa in a 45-year-old female.